Peran Pengasuh dalam Membentuk Karakter Remaja di Panti Asuhan Mahabbatul Ummi Palembang: Penelitian - Fazhia Nisha Madjid; Neni Noviza; Hartika Utami Fitri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study is entitled "The Role of Caregivers in Shaping the Character of Adolescents at Mahabbatul Ummi Orphanage, Palembang". The study aims to understand the role of caregivers in shaping adolescents’ character and to examine the development of adolescents’ character after receiving guidance at Mahabbatul Ummi Orphanage. This research uses a descriptive qualitative method with a field research approach. Data collection techniques include observation, interviews with caregivers and adolescents, and documentation. Data analysis is carried out through data reduction, data presentation, and drawing conclusions. The results show that caregivers act as educators, mentors, role models, motivators, trainers, and advisors. Character-building methods are implemented through a family-oriented approach, religious activities, reward and consequence systems, skill guidance, social activities, and assignment of responsibilities. The main challenges faced are the psychological conditions of adolescents who have experienced trauma and display a lack of discipline. The findings indicate significant character development, including increased discipline, responsibility, empathy, honesty, and emotional regulation. In conclusion, caregivers play a key role in the successful development of adolescents’ character at the orphanage through a structured and humanistic approach.